PEMANFAATAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DALAM MEMPERBAIKI PROSES PEMBELAJARAN - Hamirul, Hamirul; Apriana, Dina (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2019)
In general, the BOS funds program aims to ease the burden on the community on the financing of education in the context of quality 9-year compulsory education, and this paper aims to find out the beneficiaries of BOS funds at SD Negeri No. 24/II Dusun Koto Jayo Pelepat Ilir Kabupaten Bungo. This paper using descriptive methods with a qualitative approach and using 17 informants. From the results of the interview, it was found that Dusun Koto Jayo Pelepat Ilir Kabupaten Bungo had gone well. Where the utilization BOS funds to finance new student admission administration, purchase of teacher learning reference books and purchase the books for libraries; financing remedial and extracurricular activities; financing tests/examination and learning outcomes; power and service subscriptions; school maintenance fees; honorarium paying honor teachers and honorary education personnel; allocation of BOS funds for poor students and transport fee assistance for poor students; teacher development and profession; financing BOS fund management; and purchasing computer.